2021
DOI: 10.1101/2021.01.28.428713
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spatial organization of transcript elongation and splicing kinetics

Abstract: SummaryThe organization of the genome in three-dimensional space has been shown to play an important role in gene expression. Specifically, facets of genomic interaction such as topologically associated domains (TADs) have been shown to regulate transcription by bringing regulatory elements into close proximity1. mRNA production is an intricate process with multiple control points including regulation of Pol II elongation and the removal of non-coding sequences via pre-mRNA splicing2. The connection between ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 47 publications
(77 reference statements)
2
9
0
Order By: Relevance
“…As predicted, we observed a strongly significant (P < 2.2e-16) correlation between RNA pol II spawn rate and TPM in DMSO-, GSK591-, and MS023-treated cells (ρ = 0.50, 0.51, 0.51, respectively) (Suppl. Figure 3a) (Casill et al 2021). Consistent with previously published reports, a comparison of splicing rates within each condition confirmed that constitutive introns splice faster than cassette exons as well as alternative 5' and 3' splice sites (Suppl.…”
Section: Prmt-dependent Changes In Co-transcriptional Splicing Do Not Reflect Changes In Mrnasupporting
confidence: 91%
See 2 more Smart Citations
“…As predicted, we observed a strongly significant (P < 2.2e-16) correlation between RNA pol II spawn rate and TPM in DMSO-, GSK591-, and MS023-treated cells (ρ = 0.50, 0.51, 0.51, respectively) (Suppl. Figure 3a) (Casill et al 2021). Consistent with previously published reports, a comparison of splicing rates within each condition confirmed that constitutive introns splice faster than cassette exons as well as alternative 5' and 3' splice sites (Suppl.…”
Section: Prmt-dependent Changes In Co-transcriptional Splicing Do Not Reflect Changes In Mrnasupporting
confidence: 91%
“…The inverse relationship on RI by Type I or PRMT5i in addition to their TES-proximal location, shorter length, and weaker splice sites led us to investigate the kinetics of co-transcriptional splicing. To accomplish this, we used Splicing Kinetics and Transcript Elongation Rates by Sequencing (SKaTER seq) (Casill et al 2021). As splicing changes are present as early as two days following GSK591 or MS023 treatment, we used this time point of PRMTi for our analysis.…”
Section: Prmt-dependent Changes In Co-transcriptional Splicing Do Not Reflect Changes In Mrnamentioning
confidence: 99%
See 1 more Smart Citation
“…The inverse relationship on RI by Type I or II inhibition in addition to their TES-proximal location, shorter length, and non-canonical splice sites led us to specifically investigate the kinetics of co-transcriptional splicing. To accomplish this, we used Splicing Kinetics and Transcript Elongation Rates by Sequencing (SKaTER seq) ( Casill et al, 2021 ). A brief overview of the method follows.…”
Section: Resultsmentioning
confidence: 99%
“…(2) elongation rate, (3) splicing rate, and (4) transcript cleavage rate-is calculated using a comprehensive model that determines the rates that best fit the sequencing coverage (Casill et al 2021).…”
Section: Prmt-dependent Changes In Co-transcriptional Splicing Do Not Reflect Changes In Poly(a) Rnamentioning
confidence: 99%